KEGIATAN LAYANAN KELOMPOK BELAJAR MANDIRI DIMASA PANDEMI - Vira Nanda Atikah; Mohammad Syaiful Pradana (LPPM Universitas Islam Darul 'Ulum Lamongan, 2022)
The Covid-19 virus has an impact on all fields including education. All face-to-face activities must be stopped so that educational activities are carried out at home using an online system. This online learning process is switched by students to play at any time regardless of learning, because there is no face-to-face meeting by students and teachers. So that in this online learning, parents hope that there are people to teach their children to learn at home. With the Unisda Thematic KKN, it reduces parents' anxiety in overcoming student laziness